2019
DOI: 10.1186/s12889-019-7013-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for malnutrition among school-aged children: a cross-sectional study in rural Madagascar

Abstract: Background For over 20 years, Madagascar has been challenged by continued high prevalence of stunting, underweight and wasting among children under 5 years of age. Yet, nutritional status of post-under-five age group has never been assessed in the country, despite its importance in relation not only to physical health but also to cognitive capacity and educational achievements of children. This study aims to estimate prevalence of malnutrition among schoolchildren aged 5–14 years in Madagascar. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 12 publications
2
33
4
Order By: Relevance
“…Future studies among populations in similar settings may need to consider measuring the potential influences of such variables. Previous studies have found socioeconomic status [61,62] and older participant's age [62,63] to be correlates of thinness among children of this age group. Because thinness, which measures the nutritional status of children above five years of age and adolescents, is generally not an indicator prioritized globally [62], it is rarely monitored nor reported, hence the few available comparable data.…”
Section: Discussionmentioning
confidence: 91%
“…Future studies among populations in similar settings may need to consider measuring the potential influences of such variables. Previous studies have found socioeconomic status [61,62] and older participant's age [62,63] to be correlates of thinness among children of this age group. Because thinness, which measures the nutritional status of children above five years of age and adolescents, is generally not an indicator prioritized globally [62], it is rarely monitored nor reported, hence the few available comparable data.…”
Section: Discussionmentioning
confidence: 91%
“…Very few studies have addressed nutritional issues of school-going children to assess the magnitude of the problem. [3] In several countries the coexistence of the paradoxical situation of adult obesity with childhood malnutrition has been noted. Number of studies has shown that many households, particularly in middle-income countries, contain both underweight and obese individuals, which is described as the 'dual burden' of malnutrition [4].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity has increased rapidly in almost all countries, and these country-speci c trends are now coalescing to create a true pandemic. This pandemic is penetrating the poorest nations in the world mainly among the urban middle-aged adults and younger age groups [3]. Childhood obesity is also increasing in Sri Lanka with 14-15% prevalence of overweight and obesity among 8-12-year-old school children within the Colombo Municipal area and the world bank report in 2016 estimates that 2% of the under ve-year-old children to be affected [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A literature search was done in Pubmed using the keywords and most have addressed under nutrition in children under-5-year of age. Very few studies have addressed nutritional issues of school-going children to assess the magnitude of the problem [3]. In several countries the coexistence of the paradoxical situation of adult obesity with childhood malnutrition has been noted.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity has increased rapidly in almost all countries, and these countryspeci c trends are now coalescing to create a true pandemic. This pandemic is penetrating the poorest nations in the world mainly among the urban middle-aged adults and younger age groups [3]. Childhood obesity is also increasing in Sri Lanka with 14-15% prevalence of overweight and obesity among 8-12year-old school children within the Colombo Municipal area and the world bank report in 2016 estimates that 2% of the under ve-year-old children to be affected [7,8].…”
Section: Introductionmentioning
confidence: 99%